Marketing digital y su incidencia en el reconocimiento de marca del Centro Médico Santa Isabel, ciudad de Guayaquil - Broncano Chávez, Sergio Antonio (2023)
This degree work focuses on the analysis and improvement of the brand recognition of the Centro Médico Santa Isabel, a health institution located in the city of Guayaquil. A significant lack is identified in its visibility and positioning in the competitive healthcare market, attributed to increasing competition and the absense of a solid digital presence. In order to address this problem, a Digital Marketing Strategy is proposed to increase brand recognition and attract new patients. The strategy is based on an exhaustive analysis of data collected through surveys, interviews and bibliographic review, to understand the needs and preferences of users and the relevance of social networks in decisionmaking. The implementation of the strategy includes the creation of visually attractive content on virtual platforms, focusing on infographics and other relevant content to establish a meaningful connection with the target audience. Likewise, it seeks to optimize the website through a landing page that facilitates access to services and appointment scheduling, and the integration of communication channels is promoted for personalized and efficient attention.